Optimalisasi Keuntungan Penjualan Mieso Ayam Kriuk Menggunakan Program Linear Metode Simpleks (Studi Kasus: Mieso Ayam Kriuk Jl.Padang Bulan) - Sari, Afifah Maulinda; Putra, Erlangga Permana; Rambe, Lailatul Fauza; Sari, Indah Tiara; Prayogi, Dimas Ilham (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The food or culinary business is a business that can grow rapidly and will always be sought after by the public, because food needs are primary needs that must be met. This article discusses the optimization of Miso Ayam Kriuk sales profits using the simplex method in a linear program. Miso Ayam Kriuk, as a food product that is increasingly in demand, requires the right strategy to maximize profits in the midst of fierce market competition. Through systematic measures, including the preparation of simplex tables and iterations, a solution is obtained that provides maximum profits. The data collection technique in this study includes the use of primary data obtained through observation, interviews, or distribution of questionnaires to relevant sources. The analysis technique used is linear programming using the simplex method. The results of the study show that the function has reached optimal conditions. Therefore, the calculation is stopped after all values in the objective function become positive indicating that the maximum profit (Zmax) is Rp.800,000,-. Based on the results of this study, it shows that the application of the simplex method not only improves production efficiency but also provides insight for business actors in dealing with market dynamics.